Combined administration of alpha1-adrenoceptor antagonist prazosin and beta-blocker propranolol impairs spatial avoidance learning on a dry arena - Petrásek, Tomáš; Doulames, Vanessa; Prokopová, Iva; Valeš, Karel; Stuchlík, Aleš (Behavioural brain research, 2010)
Spatial learning is a widely studied type of animal behavior often considered as a model of higher human cognitive functions. Noradrenergic receptors play a modulatory role in many nerve functions, including vigilance, attention, reward, learning and memory. The present study aimed at studying the effects of separate or combined systemic administration of the alpha1-adrenergic antagonist prazosin (1 and 2 mg/kg) and beta-blocker propranolol (5 and 20 mg/kg) on the hippocampus-dependent learning in the active allothetic place avoidance (AAPA) task. Both centrally active drugs impaired spatial learning when administered together, exerting no effect in separate applications. Locomotion was impaired only in a combined application of higher doses of both drugs (2 mg/kg prazosin and 20 mg/kg propranolol). These results suggest an in vivo interaction between these two types of receptors in spatial navigation regulation.
Keywords: potkani Long-Evans; Propranolol; poruchy učení; Analysis of Variance; alfa blokátory; zvířata; Learning Disabilities; Rats; propranolol; Space Perception; Behavior, Animal; Motor Activity; učení vyhýbat se; Adrenergic beta-Antagonists; beta blokátory; pohybová aktivita; chování zvířat; mužské pohlaví; fixní kombinace léků; Drug Combinations; vnímání prostoru; Adrenergic alpha-Antagonists; analýza rozptylu; krysa rodu Rattus; prazosin; Animals; Rats, Long-Evans; Avoidance Learning; Male; Prazosin